Digital Entrepreneurship Intention Among Undergraduate Students - Adib Hamdani, Abdul Rahman (2023)
Digital entrepreneurship has emerged as a dynamic force driving innovation and economic growth in the modern world. This study explores the intention of digital entrepreneurship among students at UUM. Digital entrepreneurship refers to the ability to identify and capitalize on opportunities in the digital realm, transcending traditional boundaries through creative thinking, interdisciplinary collaboration and a proactive mindset. This research also investigates the relationship between digital entrepreneurship education, digital entrepreneurship knowledge and social media use on digital entrepreneurship intention. The lack of research by previous researchers has prompted researchers to conduct this study. The survey questionnaire was distributed using an online questionnaire to undergraduate students of Universiti Utara Malaysia. A total of 219 usable questionnaires were used for analysis. Direct relationships were analyzed using the PLS-SEM method. The results of the study show that digital entrepreneurship education, digital entrepreneurship knowledge and the use of social media have a significant relationship with digital entrepreneurship intention. This proves that the intention of digital entrepreneurship among UUM students is very high. Finally, management implications, study limitations and future research recommendations are discussed.